2008
DOI: 10.1111/j.1556-4029.2008.00723.x
|View full text |Cite
|
Sign up to set email alerts
|

Motor Vehicle Collisions and Their Demographics: A 5‐Year Retrospective Study of the Hamilton‐Wentworth Niagara Region*

Abstract: This retrospective study examined population demographics associated with motor vehicle collision (MVC) fatalities over a 5-year period in the Hamilton-Wentworth Niagara region. Variables were drawn from the five factors proposed by Fierro (1) for investigating deaths caused by transportation: human, chemical, environmental, vehicular, and highway. Factors analyzed included age, gender, position to the vehicle, site(s) of injury, toxicology, environmental contributors, and vehicular findings. From 1999 to 2004… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 47 publications
(75 reference statements)
0
9
1
Order By: Relevance
“…The lack of association between day of the week and fatal collisions on Ontario’s highways is not consistent with previous research by Lemieux who reported that MVCs in the Hamilton-Wentworth Niagara Region of Ontario that resulted in fatalities occurred during Fridays and Sundays, on city and rural roads as well as highways [12]. Other studies compared fatality rates in different days of the week; however, they compared weekdays vs. weekend days rather than each day individually [5,17,22].…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…The lack of association between day of the week and fatal collisions on Ontario’s highways is not consistent with previous research by Lemieux who reported that MVCs in the Hamilton-Wentworth Niagara Region of Ontario that resulted in fatalities occurred during Fridays and Sundays, on city and rural roads as well as highways [12]. Other studies compared fatality rates in different days of the week; however, they compared weekdays vs. weekend days rather than each day individually [5,17,22].…”
Section: Discussioncontrasting
confidence: 55%
“…Further, Turner and McClure revealed that men scored significantly higher than females in the ‘Driver Aggression’ and ‘Risk Acceptance’ scales [19]. Lemieux reported an increased rate of fatalities amongst male drivers compared to females [12]. However, this finding is not completely consistent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This crash type is understood to become less frequent with age relative to minor crashes. Certainly younger drivers tend to have more severe crashes than older drivers [ 159 , 160 ]. Accordingly, the association between severe crashes and traffic offences could diminish as they become relatively less common.…”
Section: Discussionmentioning
confidence: 99%
“…This crash type is understood to become less frequent with age (and driving experience) relative to minor crashes. Certainly younger drivers tend to have more severe crashes than older drivers (Blows, Ameratunga, Ivers, Lo, & Norton, 2005;Lemieux, Fernandes, & Rao, 2008). Accordingly, the association between severe crashes and traffic offences could diminish as they become relatively less common.…”
Section: The Relationship Between Crashes and Traffic Offencesmentioning
confidence: 99%